The groESL ISR sequence-based species-specific identification of GRAS and non-GRAS Lactiplantibacillus as an alternative to 16S rRNA sequencing. (July 2021) - Lee, Jong Min; Park, So Hee; Jin, Chun-Zhi; Kang, Min-Kyoung; Park, Dong-Jin; Kim, Chang-Jin
Abstract: The untranscribed DNA sequences of the intergenic spacer regions (ISR) in the groESL were analyzed to resolve the ambiguity within phylogenetically close GRAS and non-GRAS species. The sequencing results of amplified polymerase chain reaction (PCR) products using groESL-ISR-specific primers accurately distinguished L . plantarum and L . pentosus, which were not distinguished by 16 S rRNA sequences. Furthermore, the 20 selected major probiotics species were divided into several groups according to the length (22–91 bp) and homology (65–99%) of their ISR sequences, and this discrimination was consistent with core-genome-based differentiation. Therefore, ISR sequence-based species identification showed more accurate results than 16 S rRNA sequence-based identification and represented genome-based speciation. Highlights: L. plantarum and L. pentosus cannot be distinguished by the 16 S rRNA sequence. The groESL operon sequences are species-specific. The groESL operon sequences represented whole-genome-based taxonomy. The groESL ISRs are proposed as a target sequence alternative to 16 S rRNA sequencing. In this report, ISR sequences of probiotics and universal primers for PCR amplification are provided.